Malaysian takaful reporting from a maqasid shariah perspective - Alias, Ahmad Zoolhelmi; Sulaiman, Maliah; Mohd Ariffin, Noraini; Abu Bakar, Intan Suryani (Center for Islamic Philanthropy & Social Finance, 2023)
The concept and goals of takaful are based on the objectives of Islamic law, which are centred on the five dimensions of maqasid Shariah that are essential to the life of a Muslim. The application of takaful in the Muslim community appears to have a significant relationship with the attainment of Shariah objectives. The study intends to investigate the extent of Takaful reporting in Malaysia and its relationship to maqasid shariah. The disclosure index was created using the three perspectives of Islamic accountability (Shariah, social, and financial) as well as takaful-specific information. The checklist items consist of 124 items: 67 mandatory items and 57 voluntary items. These items are classified as financial reporting; Shariah compliance and governance; corporate governance; takaful policy requirements; Family Takaful; takaful undertaking solvency requirements; risks and enterprise risk management. Takaful operators disclosed 95% of the total mandatory disclosure on average. In terms of voluntary disclosure, takaful operators disclosed 38% of total voluntary disclosure. All mandatory items are fundamental or essential (daruriyat), and takaful operators are expected to have a high level of disclosure, whereas voluntary disclosure items such as general needs information (hajiyat) and refinement information (tahsiniyat) have a lower level of disclosure.